How "situational" is judgment in situational judgment tests? - KRUMM, Stefan (Institutional Knowledge at Singapore Management University, 2015)
Whereas situational judgment tests (SJTs) have traditionally been conceptualized as low-fidelity simulations with an emphasis on contextualized situation descriptions and context-dependent knowledge, a recent perspective views SJTs as measures of more general domain (context-independent) knowledge. In the current research, we contrasted these 2 perspectives in 3 studies by removing the situation descriptions (i.e., item stems) from SJTs. Across studies, the traditional contextualized SJT perspective was not supported for between 43% and 71% of the items because it did not make a significant difference whether the situation description was included or not for these items. These results were replicated across construct domains, samples, and response instructions. However, there was initial evidence that judgment in SJTs was more situational when (a) items measured job knowledge and skills and (b) response options denoted context-specific rules of action. Verbal protocol analyses confirmed that high scorers on SJTs without situation descriptions relied upon general rules about the effectiveness of the responses. Implications for SJT theory, research, and design are discussed.